Overoptimism and house price bubbles - Kim Abildgren; Niels Lynggård Hansen; Andreas Kuchler (Danmarks Nationalbank, 2016)
This paper explores the significance of overoptimism on house price developments in Denmark. The results indicate that house price developments historically have been partly driven by sentiments decoupled from underlying economic fundamentals, especially during strong house price booms. This underlines the need for a prudent macroeconomic stabilisation policy in periods with tight labour markets and a high degree of capacity utilisation. The paper is based on both aggregated data from the Danish Consumer Expectations Survey as well as the underlying household-level microdata behind the survey matched with administrative register data at a household level. This is the first paper that combines the use of all these three types of data. The macroeconometric part of the paper uses a standard structural VAR model to explore the historical linkages between the consumer confidence index and house prices. The analysis suggests that exogenous sentiment shocks contributed to the house price booms in both the mid-1980s and the mid-2000s. The microeconometric part of the paper finds that overoptimistic households in the 2000s were more likely to purchase real estate compared to other households, and that they leveraged more when purchasing real estate. Finally, the share of overoptimistic households involved in real estate trades was particularly large during the strong house-price boom in the mid-2000. – – I papiret undersøges betydningen af overoptimisme for boligprisudviklingen i Danmark. Der findes tegn på, at den historiske boligprisudvikling delvist har været drevet af optimisme uden baggrund i fundamentale økonomiske faktorer, især i perioder med kraftige boligprisstigninger. Det understreger nødvendigheden af en stabilitetsorienteret økonomisk politik i perioder med et stramt arbejdsmarked og en høj grad af kapacitetsudnyttelse i økonomien. Analysen er baseret på data fra de danske forbrugerforventningsundersøgelser. Der anvendes såvel aggregerede data fra undersøgelserne som de underliggende mikrodata kombineret med data fra administrative registre på husholdningniveau. Der er tale om det første papir, som kombinerer anvendelsen af alle tre typer af data. I den makroøkonometriske del af papiret anvendes en almindelig strukturel VAR-model til at undersøge de historiske links mellem forbrugertillid og boligpriser. Analysen indikerer, at eksogene stød til forbrugertilliden bidrog til opgangen i boligpriserne i såvel midten af 1980'erne som i midten af 2000'erne. Resultaterne i den mikroøkonometriske del af papiret indikerer, at overoptimistiske husholdninger i 2000'erne var mere tilbøjelige til at købe fast ejendom end andre husholdninger. De valgte ligeledes en højere belåningsgrad, når de købte fast ejendom. Endelig viser analysen, at der var en særlig høj andel af overopmistiske husholdninger, som gennemførte bolighandler under den kraftige opgang i boligpriserne i midten af 2000'erne.
Keywords: D10; D14; E31; E32; 330; Consumer sentiment; consumer confidence; house price bubbles; SVAR models; microdata